ANALISIS YURIDIS PENGISIAN JABATAN WAKIL KEPALA DAERAH DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Tri Suhendra Arbani (Wacana Hukum, 2018)
Based on analysis in this research, shows that: First, The Mechanism of Filling the Deputy Head of Region is done in the perspective of Government Regulation Number 49 of 2008 regarding the third amendment to Government Regulation Number 6 Year 2005 regarding the Election, Approval, Appointment and Dismissal of Regional Head and Deputy Head of Region, Second, The direct impact to the community due to the absence of a deputy head of the region can be seen from the heavy workload of regional heads in managing local governments that have many problems where it can not be resolved without the help of a representative, so that many services and development will be disrupted.